Negosiasi Pewarisan Marga “Anak Matarumah”: : Strategi dan Solusi Konflik untuk Harmoni Keluarga (Jurnal Masyarakat dan Budaya, 2023)
This study explores the evolution of patrilineal law in clan inheritance through the anak matarumah mechanism, which deviates from customary practices and is publicly recognized. It presents a qualitative analysis using primary data from in-depth interviews and field observations, along with secondary data from relevant literature. The study reveals that the anak matarumah mechanism in Ugar village has led to five models of clan inheritance: paternal lineage adherence, maternal lineage adherence, contractual clan inheritance, conflict resolution through clan inheritance, and clan inheritance upon leaving the village. These models are rooted in the Atafamaw philosophy, shaping the Ugar village's way of life. These changes reflect society's response to external values and understandings, and they involve adaptation, acculturation, and permissiveness strategies. These strategies can serve as model guidelines for local communities to persist in the face of global challenges, ensuring family continuity within the evolving patrilineal system.